(untitled) (Journal of Philosophy, Culture and Political Science, 2026)
This article explores the cultural and symbolic significance of horse domestication in the Kazakh Steppe as a foundational process in the emergence of equestrian circus traditions. Drawing on archaeological, ethnographic, and historical sources, the paper conceptualizes the taming of wild horses not merely as an economic or technological milestone, but as a profound act of culturogenesis that shaped nomadic identity, spatial practice, and embodied aesthetics. Through an analysis of the Botai culture and traditional Kazakh equestrian rituals, the article traces how early domestication practices evolved into complex performative forms that combined athleticism, ritual, and visual storytelling. These forms later influenced both national equestrian games and modern circus performances. By situating horse art within the broader framework of nomadic heritage and performative culture, the paper contributes to rethinking the genealogy of performance in Central Asia and underscores the importance of indigenous knowledge systems in shaping civilizational values and cultural memory. Keywords: Horse domestication, Culturogenesis, Equestrian circus art, Kazakh Steppe, Nomadic heritage, Performative culture